Unilateral livedo reticularis in a COVID-19 patient: Case with fatal outcome - Tusheva, Ivana; Damevska, Katerina; Dimitrovska, I; Markovska, Zorica; Malinovska-Nikolovska, Liljana (Elsevier BV / American Academy of Dermatology, 2021)
We report a case of unilateral LR in a patient, with a fatal outcome, presenting their initial and follow-up clinical and laboratory findings.
Keywords: COVID-19; livedo reticularis; skin